PENGARUH INFLASI DAN LEVERAGE TERHADAP PROFITABILITAS DAN RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Adyatmika, I Gede Putra; Wiksuana, I Gusti Bagus (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
The purpose of this study is to determine the effect of Inflation and Leverage on Profitability and Stock Return as well as knowing the ability of Profitability in mediating the influence of Inflation and Leverage to Stock Return at manufacturing companies in Indonesiai Stock Exchange. This research uses stocks of manufacturing sector companies as the object of research. The sampling of the research was conducted by proportional random sampling method and the number of samples of this study were 31 companies obtained from the Indonesia Stock Exchange website from 2012 until 2016. Hypothesis testing is done by path analysis method with the help of SPSS program. The results of the study found that (1) Inflation has a negative and significant effect on the Stock Return, (2) Leverage has a negative and significant effect on Stock Return, (3) Profitability has a positive and significant effect on Stock Return, (4) Inflation has negative and insignificant influence on Profitability, (5) Leverage has a negative and significant influence on Profitability, (6) Profitability is not able to mediate the influence of Inflation on Stock Return, (7) Profitability able to mediate the influence of Leverage on Stock Return.